ANALISIS STRES KERJA KARYAWAN DIVISI TRANSAKSI ENERGI TERHADAP KINERJA OPERASI GABUNGAN PENERTIBAN PEMAKAIAN TENAGA LISTRIK (P2TL) TAHUN 2021 (STUDI KASUS PT PLN ULP WAY HALIM) - Herlinawati, Intan; Wardianto, K. Bagus (Jurusan Administrasi Bisnis, FISIP, Universitas Lampung, 2023)
Abstract The purpose of this study is to analyze the phenomenon of work stress that occurs to employees of the Energy Transaction Division of PT PLN ULP Way Halim during the P2TL joint operation, starting from the causes of stress, the impact of stress, how to manage stress and the relationship between work stress and employee performance during joint P2TL operations. This research uses a descriptive qualitative research method with an intrinsic case study approach. Research data collection was carried out by means of observation, documentation and interviews with 5 main informants and 1 key informant. Based on the results of the study, the stress experienced by employees refers to symptoms of mild stress experienced by employees of the energy transaction division during joint P2TL operations. (1) The triggers for work stress are high workloads, role conflicts and an unsupportive physical environment. (2) The impact of stress is that employees become more sensitive to criticism, headaches, acne and digestive disorders. (3) Employees manage stress by listening to music, thinking positively, building good team communication and minimizing conflicts. (4) work stress at this level makes employee performance increase. Keywords: Job Stress, Stress Factors, Impact of Stress, Stress Management, Performance